The Comparison Between Chinese Puppet Show and Chinese-Javanese Blend Puppet Show in Indonesia - Sufianto, Agustinus; Fillysca, Fillysca; Joncicilia, Shally (Bina Nusantara University, 2011)
Since some centuries ago, Indonesia has been one of the destinations for immigrating Chinese. When the Chinese came to Indonesia, they also brought their cultures and customs. Some of them have a cultural-cross marriage with local Indonesian and brought their cultures to be introduced to local Indonesian. When the relationship between Chinese and Indonesian became stronger in some fields such as trade, education and politic, some of Chinese cultures has been adapted by local Indonesian or has been assimilated with local cultures. This adaption process was hindered when the New Order of Soeharto government had banned all Chinese culture, including anything closely related. So, the Chinese-Javanese blend puppet show that also brings Chinese culture couldn’t get any supports and its development faces difficulties. The writer using a qualitative methodology interviewed some of Chinese-Javanese puppet show artist and observation of the puppet show performance to make a comparison between Chinese puppet show and Chinese-Javanese blend puppet show in Indonesia. Chinese-Javanese puppet show or usually can be determined as Indonesian potehi puppet Show has some differences from Chinese puppet show. The differences can be found in the making of puppet, puppet profiles, performance way and stories.